2000
DOI: 10.1002/(sici)1098-2760(20000705)26:1<48::aid-mop15>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Energy model for optically controlled MESFETs

Abstract: An energy‐based transport model for the analysis of illuminated microwave active devices is presented. The model is based on the Boltzmann's transport equation, with optical carrier generation and carrier recombination accounted for. The simulation results are compared with the conventional local‐field mobility models based on drift‐diffusion formulations. It is shown that the drift‐diffusion models lose their applicability in submicrometer gate‐length devices. The presented time‐domain model has a great poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The active device model is based on the moments of the BTE obtained by integration over momentum space. The integration results in a strongly-coupled highly-nonlinear set of partial differential equations called the conservation equations (Alsunaidi 2000;Blotekjaer 1970). These equations provide a time-dependent self-consistent solution for carrier density, carrier energy and carrier momentum and are given by…”
Section: Device Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…The active device model is based on the moments of the BTE obtained by integration over momentum space. The integration results in a strongly-coupled highly-nonlinear set of partial differential equations called the conservation equations (Alsunaidi 2000;Blotekjaer 1970). These equations provide a time-dependent self-consistent solution for carrier density, carrier energy and carrier momentum and are given by…”
Section: Device Modelmentioning
confidence: 99%
“…These efforts fall in two main categories: analytical and equivalent circuit models. A recent review of these GaAs models can be found in Alsunaidi (2000) and Murty and Jit (2006). Although they provide representations of the device global operating conditions, analytical models are very well known for their simplifying assumptions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations